Basic Planning Principles of an Artificial Wetland for Rural Settlements in Cold Climate Conditions - Kuslu , Yasemin (Emerging Issues in Environment, Geography and Earth Science Vol. 5, 2023)
This chapter focuses on the planning of constructed wetlands in existing rural communities or prospective rural settlements that must be re-planned due to various elements in Turkey settings. Wetland systems are divided into two groups as natural and artificial. Artificial wetlands are one of the strategies used to recover water for domestic or agricultural purposes while minimizing environmental impact. An artificial wetland plan sample was created in this study for residential wastewater treatment in a village, which has cold climatic conditions, a projected population of 350, and a height of roughly 1750 m above sea level. Wetland area with two chambers of 0.7 m in depth, 20 m in width, and 40 m in length was identified as a consequence of the planning. The effluent water's BOD (Biological Oxygen Demand) value was determined to be 20.17 mg/L after 5.6 days of holding in the chamber.